Review of ther book entitled Discrete Communication Systems by Stevan Berber, Oxford University Press, 2021 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2023)
The book contains the theory of discrete communication systems that are presented in the form of block schematics defined by mathematical operators. For the sake of comparison, the theory of digital communication systems is added to understand better the relations between the two theories. Two generic schemes of the systems are designed that are used to develop specific discrete and digital systems as their special cases. The complementary chapters of the book contain the theory of the continuous-time and discrete-time processing of the deterministic and stochastic signal that is necessary for understanding the main chapters presenting communication systems.